A multilateral model of ecological ammensalism - numerical approach - Mohan, P Rama; Gopal, N Rama; Acharyulu, K.V.L.N (Journal of Experimental Sciences, 2012)
The paper concerns with the numerical study of a mathematical model of “A Multilateral Model of Ecological Ammensalism - Numerical Approach”. The mathematical model comprises of Ammensal-enemy species pair with (i) a constant number of Ammensal is provided with cover to protect it from enemy(ii)the enemy is provided with alternate resources in addition to the Ammensal species (iii) both the species are immigrated and migrated. The model is organized by a couple of first order non linear ordinary differential equations. The numerical illustrations of the growth equations are computed by implementing the classical Runge-Kutta method of fourth order. The relations among the cover protected constant and the dominance reversal time is investigated. Some conclusions are obtained by the results. AMS Classification: 92 D 25, 92 D 40